2021
DOI: 10.3390/agronomy11040724
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tillage and Crop Rotations in Organic and Conventional Farming Systems on Soil Organic Matter, Bulk Density and Enzymatic Activities in a Short-Term Field Experiment

Abstract: Intensive agricultural practices are leading to loss of soil fertility and overexploitation of natural resources which cause nutrients imbalance and further impair ecosystem services. Organic farming (OF), also coupled with minimum tillage and crop rotations, represents one of the strategies to limit this process and maintain soil functions. In a two-year field trial, organic farming practices, including a set of fertilizations combined with crop rotations and association with nitrogen fixing cover crops, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
3
10
0
1
Order By: Relevance
“…The observed positive correlation of β-glucosidase with OM indicates the specificity of the enzyme to soil C, which is a fraction of the total soil OM ( Meena and Rao, 2021 ). Corroborating with our result of reduced enzyme activities in the conventional farm, excessive use of chemical fertilizers has been reported to hinder soil enzyme activities ( Pittarello et al, 2021 ; Rachwał et al, 2021 ). Thus, the types of fertilizers used in plant cultivation affect changes in soil conditions, such as enzyme activities which may cause variations in the dynamics of the associated soil microbial community ( Liu and Hanlon, 2018 ; Ullah et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The observed positive correlation of β-glucosidase with OM indicates the specificity of the enzyme to soil C, which is a fraction of the total soil OM ( Meena and Rao, 2021 ). Corroborating with our result of reduced enzyme activities in the conventional farm, excessive use of chemical fertilizers has been reported to hinder soil enzyme activities ( Pittarello et al, 2021 ; Rachwał et al, 2021 ). Thus, the types of fertilizers used in plant cultivation affect changes in soil conditions, such as enzyme activities which may cause variations in the dynamics of the associated soil microbial community ( Liu and Hanlon, 2018 ; Ullah et al, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…High activity of soil enzymes, including dehydrogenase, β-glucosidase and urease activities have been reported in organic farms ( Hernandez T. et al, 2021 ; Pittarello et al, 2021 ). Extracellular enzyme production has been positively correlated with high microbial biomass and diversity in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they suggested that properties of leguminous biomass could be considered efficient drivers to define the complexity of arthropod and earthworm communities. As reported in Pittarello et al [23] main crops and cover crops can have an important and variable influence on microbial activity depending on the mix of species employed. Microbial biomass and enzymatic activities are commonly used as a tool for soil quality detection [24].…”
Section: Introductionmentioning
confidence: 80%
“…Results for SOM parameters (Table 2) such as TOC and TN were not significantly influenced in the three years of CONS management, consistent with the data reported by Muscolo et al [47] while Rakesh et al [48] in a 4-year-long experiment found a significant TOC improvement compared to conventionally managed soils. Microbial biomass and soil enzymatic activities were found to be more reliable factors to depict the soil evolution both in short periods [23,49] and long periods [50]. The significant increase in β-glucosidase activity in CONS indicated an improvement in carbon cycle and the significant differences between the managements suggest an important role of cover crops in the soil evolution under conservative management.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, soil N cycling enzymatic activity under NT was particularly intense and correlated with mineral N, in GAL, and EON availability, in SMA, indicating also greater protection of extractable organic matter in clay-loam soil (GAL) according to Alluvione et al [94], Six and Paustian [95] and Han et al [96]. On the contrary, in CT, and especially in GAL, the greater abundance of fungi and Bac + at harvest may be linked to the increase of enzymes involved in C (β-glucosidase) and N cycle (chitinase) to decompose complex organic compounds [96][97][98][99] following the results achieved from Pearson's correlation analysis and PCA. Further, it is evident that in GAL the increase in Bac + oligotrophic population is correlated with an increase in the consumption of EON, which was poorly available because protected by soil, associated with a higher enzymatic activity [89,100].…”
Section: Discussionmentioning
confidence: 99%